THE DON COSSACKS IN THE BEGINNING OF XIX CENTURY - S.G. VOSKOBOYNIKOV (Advanced Engineering Research)
In clausearticle are consideredexamined a social and economic situation on Don developed to the beginning of XIX century, and also reform spent by the Russian government and ataman M.I.Platovym during the period with 1802 for 1804.